Effect of Different Improvers on Gluten-Free Cassava Bread For Enhanced Sensory Attributes, Physical Quality and Proximate Composition - Kanu, A. N.; Okogbue, G.; Onwusiribe, C. S. (Journal of Science, Technology and Innovation Research, 2025)
The search for substitute flours and useful additives to mimic the characteristics of wheat-based bread has been spurred by the growing demand for gluten-free goods. This study assessed the impact of many hydrocolloid improvers, including carboxymethyl, gelatin, and psyllium husk. cellulose (CMC) and xanthan gum (XAG)—on the physical attributes, sensory attributes, and approximate composition of bread made using premium cassava flour (HQCF). The cassava sample used for this study was sourced from the National Root Crops Research Institute Umudike. Standard bread-making procedures were applied, after which analysis on sensory evaluation, physical quality and proximate composition were was conducted using a 20-member panel on a 9-point hedonic scale, vernier caliper and standard laboratory chemicals respectively. A wheat-based positive control (WPC) and a cassava-based negative control (CNC) were used for comparison. Results showed that bread samples with improvers exhibited varied sensory outcomes, with PSH-enhanced bread, scoring highest in texture (6.40), taste (6.10), chewiness (6.50), and overall acceptability (6.50) among the gluten-free variants, followed by CMC. GET and XAG showed moderate to low sensory acceptance. The physical parameter showed that the height, length, width and weight ranged from 8.34 to 9.58, 14.87 to 16.86, 9.33 to 73 and 471 to 598, respectively. The result showed that among the improved bread samples, samples CMS and PSH increased the height and width of the bread, while sample XAN had a low value in all physical parameters investigated. The study concludes that hydrocolloid improvers can significantly enhance the sensory attributes and physical parameters of gluten-free cassava bread, making it a viable alternative to wheat-based bread, particularly for individuals with gluten intolerance or celiac disease